How to Reduce Discrimination in the Workplace: The Case of Austria and Taiwan (R.O.C.) - Bobek, Vito; Maček, Anita; Bradler, Sarah; Horvat, Tatjana (Naše gospodarstvo/Our economy, 2018)
To intervene against discriminatory in the workplace is tremendously important because discriminatory practices have an enormous economic impact, along with a severe impact on psychological health, which can result in illnesses such as depression and burnout. Such intervention requires a multidimensional approach, including the whole organization and a systematic procedure. The aim of this paper is to offer suggestions on how to reduce discrimination in the workplace in Austria and Taiwan. To reach this aim, a qualitative study was conducted. It showed that education, active positioning of companies, leadership and diligent selection of employees, discussion and analysis, psychological support, governmental policies, and aspects of language and talking gender-wise are the most important steps to decrease or eliminate discrimination in the workplace.
Keywords: discrimination; business practices; leadership; workplace